Communication Strategies in Implementing Solid Liquid Waste Management (SLWM) Practices in Rural India with Special Emphasis on Behaviour Change Communication (International Journal of Food and Nutritional Sciences, 2021)
The concept of Solid Liquid Waste Management (SLWM) assumes great significance in terms of growing demand for sustainable development principles and overall welfare of human beings. The initiatives around SLWM are redefining living patterns in rural spaces across India. In the absence of its proper disposal, these huge dumps of wastes have a tendency to become breeding grounds for various contagious and non-contagious diseases. Lack of hygiene and sanitation practices, clean water and improper disposal of wastes becomes the major contributing factor of the total disease load within any area or region. To tackle this issue public engagement assumes great importance apart from government policies and initiatives. Public participation can be garnered through various measures and mechanisms. Communication plays an upper role in all those initiatives and strategies. It plays a key role in reaching out to public, making them part of multiple public-engagement strategies and sensitizing them about significance of health, hygiene and sanitation and the steps and strategies adopted by the government to achieve this goal. Clear, creative, comprehensible and engaging communication plans, policies and strategies need to be formulated to make related media campaigns specific and relevant. Strengthening Behaviour Change Communication efforts also need to be enhanced to achieve desired results.